Demand-Driven Propagation : Evidence from the Great Recession - Nguyen, Hu (World Bank, Washington, DC, 2015)
This paper provides empirical evidence for the Keynesian demand-driven propagation: initial rounds of job losses lead to additional rounds of job losses. The paper shows that U.S. counties with higher pre-existing exposure to tradable industries experienced larger job losses in non-tradable sectors during the Great Recession. This was arguably because laid-off tradable workers cut their consumption, which hurts local non-tradable firms. The finding is not driven by exposure to the construction sector, by the collapse in house prices, or by credit supply problems. In addition, the spillover is stronger when the focus is on the job losses of more income-elastic non-tradable sectors.